2015
DOI: 10.2147/ppa.s87659
|View full text |Cite
|
Sign up to set email alerts
|

Associations of quality of life, pain, and self-reported arthritis with age, employment, bleed rate, and utilization of hemophilia treatment center and health care provider services: results in adults with hemophilia in the HERO study

Abstract: IntroductionSevere hemophilia and subsequent hemophilic arthropathy result in joint pain and impaired health-related quality of life (HRQoL). Assessment of HRQoL in persons with hemophilia (PWH), including underlying factors that drive HRQoL differences, is important in determining health care resource allocation and in making individualized clinical decisions.AimTo examine potential associations between HRQoL, pain interference, and self-reported arthritis and age, employment, activity, bleed frequency, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
177
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(193 citation statements)
references
References 24 publications
11
177
1
4
Order By: Relevance
“…US data from the HERO study also demonstrated that physical therapist involvement was more common in people with better quality of life scores (EQ‐5D) and less pain. Social worker and nurse involvement were more common in people with increasing pain and disability . International data from the HERO study reported information from 453 parents of children with haemophilia receiving care in HTCs globally. The nurse was involved in the care of ˜70% of respondents, and a social worker was involved in care of ˜30% of respondents.…”
Section: Resultsmentioning
confidence: 99%
“…US data from the HERO study also demonstrated that physical therapist involvement was more common in people with better quality of life scores (EQ‐5D) and less pain. Social worker and nurse involvement were more common in people with increasing pain and disability . International data from the HERO study reported information from 453 parents of children with haemophilia receiving care in HTCs globally. The nurse was involved in the care of ˜70% of respondents, and a social worker was involved in care of ˜30% of respondents.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, most patients with severe haemophilia have limited access to adequate treatment, as they live primarily in developing countries . Without adequate treatment, haemophilia can be extremely debilitating and can present a significant economic burden on patients, caregivers and society, influencing education and employment . Pain and suffering are important aspects in this disease, which have been associated to decreased quality of life …”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, in patients with severe haemophilia, <15% experience pain in only 1 or 2 regions, while more than 35% report pain in at least 5 regions. 2 Moreover, in patients with severe haemophilia, <15% experience pain in only 1 or 2 regions, while more than 35% report pain in at least 5 regions.…”
Section: Introductionmentioning
confidence: 99%